“Asking for help is a strength”—how to promote undergraduate medical students’ teamwork through simulation training and interprofessional faculty - Michaela Kolbe; Michaela Kolbe; Jörg Goldhahn; Mirdita Useini; Bastian Grande; Bastian Grande (Frontiers in Psychology, 2023)
The ability to team up and safely work in any kind of healthcare team is a critical asset and should be taught early on in medical education. Medical students should be given the chance to “walk the talk” of teamwork by training and reflecting in teams. Our goal was to design, implement and evaluate the feasibility of a simulation-based teamwork training (TeamSIM) for undergraduate medical students that puts generic teamwork skills centerstage. We designed TeamSIM to include 12 learning objectives. For this pre-post, mixed-methods feasibility study, third-year medical students, organized in teams of 11–12 students, participated and observed each other in eight simulations of different clinical situation with varying degrees of complexity (e.g., deteriorating patient in ward; trauma; resuscitation). Guided by an interprofessional clinical faculty with simulation-based instructor training, student teams reflected on their shared experience in structured team debriefings. Using published instruments, we measured (a) students’ reactions to TeamSIM and their perceptions of psychological safety via self-report, (b) their ongoing reflections via experience sampling, and (c) their teamwork skills via behavior observation. Ninety four students participated. They reported positive reactions to TeamSIM (M = 5.23, SD = 0.5). Their mean initial reported level of psychological safety was M = 3.8 (SD = 0.4) which rose to M = 4.3 (SD = 0.5) toward the end of the course [T(21) = −2.8, 95% CI −0.78 to-0.12, p = 0.011 (two-tailed)]. We obtained n = 314 headline reflections from the students and n = 95 from the faculty. For the students, the most frequent theme assigned to their headlines involved the concepts taught in the course such as “10 s for 10 min.” For the faculty, the most frequent theme assigned to their headlines were reflections on how their simulation session worked for the students. The faculty rated students’ teamwork skills higher after the last compared to the first debriefing. Undergraduate medical students can learn crucial teamwork skills in simulations supported by an experienced faculty and with a high degree of psychological safety. Both students and faculty appreciate the learning possibilities of simulation. At the same time, this learning can be challenging, intense and overwhelming. It takes a team to teach teamwork.